ANALISIS PENGARUH KEPUASAN DAN LOYALITAS PENGGUNA BLACKBERRY DI YOGYAKARTA - , R. Jati Ratmoko, Dr. Sahid Susilo Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to determine the relationship between customer satisfaction and loyalty. The target is to define a conceptual framework to analyze the relationship between satisfaction, loyalty and buying behavior of the customers themselves. This research is a quantitative study using survey methods. This study uses primary data. Location of the study is in the province of Yogyakarta Special Region. The object of this study is a cell phone or mobile phones manufactured by RIM (Research in Motion), especially all the products under the brand name Blackberry. The data analysis technique used in this study is a descriptive analysis, regression analysis and classical assumptions. The results showed that the Blackberry product consumers feel satisfaction in using the product will be more loyal and will further encourage the purchase of the company's products. Customer loyalty and customer satisfaction is the driving factor in the buying behavior of the respondents Blackberry products in the city. Customers who have felt satisfaction in using the product, the brand will look like when he'll buy another product. Greater satisfaction and long will accumulate a loyal customer in purchasing the product Blackberry. Results of testing the effect of two independent variables together on purchasing behavior suggests the third hypothesis is acceptable, so the variable customer loyalty and customer satisfaction a positive effect on purchasing behavior. These results imply that the higher the customer loyalty and customer satisfaction, the higher the purchasing behavior. After testing the effect of partially found there, so after the effects together, is found to influence significantly. This shows that customer satisfaction and customer loyalty proven effect partially or jointly on buying behavior.